2008
DOI: 10.1002/ijc.23580
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR‐23a∼27a∼24 decreases transforming growth factor‐beta‐induced tumor‐suppressive activities in human hepatocellular carcinoma cells

Abstract: Transforming growth factor-beta (TGF-beta) plays a dual and complex role in human cancer. In this report, we observe a specific set of MicroRNAs (miRNAs) changed in response to TGF-beta in human hepatocellular carcinoma (HCC) cells by miRNA microarray screening. A cluster of miRNA, miR-23a 27a 24, is induced in an early stage by TGF-beta in Huh-7 cells. Knockdown of Smad4, Smad2 or Smad3 expression by RNA interference can attenuate the response of miR-23a 27a 24 to TGF-beta addition, indicating that this induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
168
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(175 citation statements)
references
References 24 publications
6
168
0
1
Order By: Relevance
“…Therefore, the results support the possibility that the accumulation of these miRs is intended to protect ESCs from an inappropriate apoptosis induced by BMP4. The anti-apoptotic role of these miRs was already described in other experimental systems [32][33][34] and was also confirmed in our experiments where ESCs were exposed to genotoxic stress (Figure 4e). However, the mechanism through which the miRs exert this function is not clearly understood.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the results support the possibility that the accumulation of these miRs is intended to protect ESCs from an inappropriate apoptosis induced by BMP4. The anti-apoptotic role of these miRs was already described in other experimental systems [32][33][34] and was also confirmed in our experiments where ESCs were exposed to genotoxic stress (Figure 4e). However, the mechanism through which the miRs exert this function is not clearly understood.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have shown that miR-27a contributes to the transformation or maintenance of a malignant state in breast cancer cells or gastric adenocarcinoma by targeting mRNAs of the transcription factor FOXO1 (Guttilla and White, 2009) and the membrane protein prohibitin (Liu et al, 2009). In hepatocellular carcinoma cells, upregulation of miR-27a confers the cells resistant to apoptosis induced by transforming growth factor-b (Huang et al, 2008). Moreover, miR-27a modulates the malignant biological behavior of pancreatic cancer cells by targeting sprouty2 mRNA, a crucial molecule involved in the Ras/MAPK signaling pathway (Ma et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-128 inhibits glioma cell proliferation by targeting the transcription factor, E2F3a (13), and miR-200c and miR-141 (members of the miR-200 family) are important regulators of the epithelial to mesenchymal transition in normal and cancer cells (7,14). Furthermore, fragments of miRNA can be found and measured in the serum of patients with cancer, and could potentially act as a novel class of biomarkers for diagnosis or cancer staging; for instance, tumor-suppressive activities in human hepatocellular carcinoma cells are decreased by up-regulation of miR23a~27a~24 (15). However, the complexity of the structures and cloning processes for miRNAs has prevented the analysis of large numbers of clinical samples.…”
Section: Introductionmentioning
confidence: 99%